Determination of toxic organic chemicals in natural waters, sediments and soils : determination and analysis - Crompton, T. R. (Thomas Roy) (Academic Press, 2019)
Determination of Toxic Organic Chemicals in Natural Waters, Sediments and Soils: Determination and Analysis reviews the latest techniques for the determination and assessment of both current and emerging organic compounds in a range of important environmental contexts. A wide range of organic compounds in non-saline waters are discussed in the opening chapters, including hydrocarbons, surface active agents and volatile organic compounds. This is followed by multiorganics, pesticides and organometallic compounds in non-saline waters. Organic compounds in aqueous precipitation are then explored before the book goes on to discuss compounds in soils, including extraction techniques, insecticides, herbicides and fungicides, and organometallic compounds. Finally, the concluding chapters focus on compounds in sediments, providing readers with the latest information in the field and supporting them as they address the important issue surrounding organic material throughout ecosystems.